DESIGN AND MANUFACTURE OF AN OMNI-WHEEL ROBOT WITH A DUAL ARM MANIPULATOR - MUSTAFA, HEMIN JAMAL MUSTAFA (Fırat Üniveristesi, 2019)
Son yıllarda, çeşitli hareket kabiliyetine sahip Otonom Robotlar, farklı alanlarda kullanmak için üretilmiştir. Bu tezde Omni tekerlere sahip bir robot tasarlanmış ve üretilmiştir. Omni tekerli robotları çok yaygındır, çünkü herhangi bir yöne hareket edebilme yeteneğine sahiptirler ve bazıları kıskaçlar veya kollarla donatılmıştır. Bu tür robotlarda görülen yaygın bir problem, robotun tutucusunun, yüksek kotlarda depolanan öğelere ulaşmak için çok kısa olmasıdır. Bu araştırmanın amacı, gövdesini genişletmeye gerek kalmadan yüksekteki nesnelere ulaşabilen uzun kolları olan bir robot tasarlamak ve üretmektir. Ayrıca, bu robotu kablosuz iletişim yetenekleriyle donatmak bu araştırmanın amacı olmuştur. Kablosuz radyo frekans kontrollü yetenekler, robotun uzak bir konumdan veri alma ve iletme işlevini daha da artıracaktır.

In the latest years, Autonomous Robots, which can operate using variety of different movement, have be developed manufactured and used in various occasions and occupations in this thesis a robot has been designed and created which uses Omni Wheels. Omni wheels robots are very common, since they do have the ability to move in any direction, and some are equipped with grippers or/and arms. A common problem that exists in such robots is that the robot's gripper is too short to reach items that are stored in high elevations, for example above a table. Given that most items are stored in higher places, the purpose of this research has been to design and create a robot that has large arms that can reach objects that are above its height without the need of expanding its body and without the risk of tripping over. Furthermore, it has been the objective of this research to equip this Omni robot with wireless radio capabilities. This wireless radio controlled capabilities would further enhance the function of the robot to obtain and transmit data from a remote position.
Çift Kollu Manipülatöre Sahip Omni Tekerlekli Bir Robotun Tasarımı ve İmalatı
Keywords: Mekatronik Mühendisliği